Mediatization of Gender: An Audience Perspective on Presentation of Women in Pakistani Ads - Hassan Shehzad; Shane Zahra; Syed Muhammad Bilal Shah, (ASIAN Journal of International Peace & Security (AJIPS), 2022)
Different segments of life have an influence on society, such as cultural values, environment, and relational behavior. Media and advertising represent our current societal social standards while also having the power to alter our views by how things are presented. It is seen as an effective component for molding and propagating societal ideas. Advertisements are one of the strategies used to communicate with the general public in order to disseminate the ideology that behind the messaging. For feminists, gender analysts, academics, and the general public, stereotypical women roles portrayal has long been an essential component of the discussion. Many researchers have been carried out to investigate this phenomenon, and they have yielded substantial results but still this phenomenon is debatable. The goal of this study was to look into the roles of women in Pakistani media advertising. The survey research method is used as a research design for this research. Data was collected from the Pakistani people (from Islamabad city). The sample size of the study was 200 and simple random sampling technique was used for data collection. The finding of the study shows that Pakistani media is not representing the real image of the women. The women are depicted in Pakistani media advertisement like a showpiece. The findings also indicated women are objectified in advertisement as sex object and used for gaining the attention of the peoples. This study is helpful for the media industries for revision of their policies regarding the women role.